Morphological identification of hookworm species in five regions of Cameroon - Dongmo C.N.; Jatsa H.B.; Tchuem Tchuente L-A (Helminthologia)
Infections with hookworms (Necator americanus and Ancylostoma duodenale) remain a major public health problem in low- and middle-income countries. However, the information about the distribution of each species is inaccurate in many countries since their traditional diagnosis is based only on the identification of eggs in stool under a microscope. We aimed to identify the prevalence of hookworm species using morphological stools to identify L3 larvae to gain insights into the distribution of both species in five regions of Cameroon. Samples were collected from schoolchildren in five regions and 34 subdivisions of Cameroon and examined using the Kato-Katz method. We randomly selected a total of 157 samples among hookworm's positive stool samples. They were cultured using the Harada-Mori test-tube technique. The morphological identification of a total of 8063 isolated hookworm filariform larvae L3 was conducted following established criteria. The sensitivity rate to the Harada-Mori technique was 58 %. Among the 8063 L3 larvae identified during this study, 230 (2.95 %) of L3 larvae were identified as A. duodenale, and 7833 (97.15 %) of L3 larvae were identified as N. americanus. A. duodenale was observed only in the Mouanko subdivision in the Littoral region. The complementary use of the Kato Katz and the Harada-Mori culture techniques to screen hookworm infections contributes to the differentiation of N. americanus and A. duodenale as the two hookworm species in Cameroon. An extended molecular study in the localities where only N. americanus has been identified is necessary to reach more conclusions on the distribution of hookworm species in Cameroon.